IMMUNOLOGICAL STUDIES WITH THE VIRUS OF INFLUENZA - Francis, Thomas (The Rockefeller University Press, 1935)
Following infection with the virus of influenza, both ferrets and mice develop a state of active immunity to reinfection. The serum of these animals contains neutralizing antibodies, as evidenced by the capacity of the serum to confer passive protection to mice against infection with the P.R.8 and Phila. strains of the virus of human influenza. Rabbits which are apparently insusceptible to infection with the virus of influenza produce specific antibodies in response to repeated injection of virus-containing material. The serum of immunized rabbits affords passive protection to mice against mouse-virulent virus. Although the subcutaneous or intraperitoneal injection of the living virus does not produce infection in mice, animals so treated acquire active immunity against subsequent infection by the intranasal route. Neutralization tests with the serum of patients before and after recovery from influenza, pneumonia and the common cold indicate that neutralizing antibodies arise as a specific response to infection with the virus of influenza. The immunological identity of strains of influenza virus recovered from human sources has been established, and the possible existence of strains of related, but not identical, antigenic structure is discussed.